Incidental Noncardiac Findings at Coronary Computed Tomography Angiography - Durmaz, Emine Şebnem; İncesu Gündüz and Erden, Tolga Kaan and Yağcı, Lara and Öztürk Admir and Hasanbaşoğlu, Berivan Tuğba and Arasan, Helin Nur and Durmaz, Eser (Cerrahpaşa Medical Journal, 2025)
Objective: Coronary computed tomography angiography (CCTA) is one of the most used non-invasive imaging modalities for assessing obstructive coronary artery disease (CAD). Beyond the coronary arteries, CCTA also evaluates the structures adjacent to the heart and commonly diagnoses noncardiac pathologies. This study aimed to investigate the incidence and clinical significance of noncardiac findings in patients who underwent CCTA with the suspicion of obstructive CAD. Methods: Patients who underwent CCTA between 2021 and 2024 were retrospectively included. Patients with prior diagnoses of noncardiac pathologies were excluded from the study. Noncardiac findings were assessed according to their clinical significance and/or relation to the patient’s complaints. Results: A total of 2208 patients were screened, and 2103 patients were included after excluding ineligible patients. Among 2103 CCTA imaging, 615 noncardiac findings were detected in 586 patients (27.8% of the study population). In 88 patients, noncardiac findings were possibly related to patient complaints, and only 5 patients among 88 patients demonstrated obstructive CAD. Hence, in 83 patients, noncardiac findings are considered the cause of complaints. Fifty-six findings were thought to be clinically significant and underwent further work-up. Among 56 patients, 3 patients were diagnosed with lung cancer, 1 patient with lymphoma, 1 patient with neuroendocrine carcinoma, 1 patient with peripheral nerve sheath tumor, and 1 patient with sarcoidosis. Conclusion: The results demonstrated that CCTA is a feasible technique not only for assessing CAD but also for helping to differentially diagnose chest pain. In addition, incidental findings might be clinically significant and lead to early diagnosis of life-threatening conditions. Cite this article as: Durmaz EŞ, İncesu G, Erden TK, et al. Incidental noncardiac findings at coronary computed tomographyangiography. Cerrahpaşa Med J 2025, 49, 0039, doi:10.5152/cjm.2025.25039.